Semiotic dynamics, ethnomethodology... and after? Confrontations, syntheses and openings (Signifiances (Signifying), 2022)
Backed by the consideration of the activity and activism of the actors of communication, what I retain under the term "semiotic dynamics" aims to be interested in the processes of putting meaning, of developing meaning, but also transformation of form(s) on the margins of linguistic and 'langagières' approaches. Its concepts having already been widely presented elsewhere, I propose here, after having summarized them, to confront them with those which are specific to the ethnomethodological perspective (born at the margins of sociological research) insofar as a certain conceptual parallelism seems link the two approaches. Secondly, I will note some orientations of a post-Greimassian semiotics which, on certain points, seems to be likely to intersect with this problematic of semiotic dynamics.